3D Porous NaTi2(PO4)3 with Long Life, Superior Rate, and Low‐Temperature Properties. Issue 7 (17th May 2019) - Hu, Qiao; Liao, Jiaying; Xu, Rui; He, Xiaodong; Wang, Junru; Ding, Xiang; Chen, Chunhua
Abstract : Reticular 3D porous NaTi2 (PO4 )3 thin films decorated with reduced graphene oxide (NTP@rGO) on a nickel foam substrate are synthesized by electrostatic spray deposition technique. The interconnected pore networks and highly conductive carbon frameworks not only facilitate the kinetics of sodium‐ion diffusion but also provide abundant reaction interfaces. The NTP@rGO electrode shows superb rate performance with a charge capacity of 109.4 mAh g −1 at 100 C, i.e., 96.8% retention of its capacity at 0.5 C. After 2500 cycles at 20 C, the reversible capacity still reaches 93.1 mAh g −1 with a very slow capacity decay of 0.0045% per cycle. Even at −10 °C, NTP@rGO still delivers 98 mAh g −1 at 50 C and 92.5 mAh g −1 at 100 C. Such a composite anode combines the advantages of batteries and supercapacitors, showing great potential applicability for high‐energy and high‐power sodium‐ion storage. Abstract : Reticular 3D porous NaTi2 (PO4 )3 thin films decorated with reduced graphene oxide (NTP@rGO) on a nickel foam substrate are synthesized by electrostatic spray deposition technique. The electrochemical properties of this novel NTP@rGO combine the advantages of both rechargeable batteries and supercapacitors.